العلاقات الأسرية بالمغرب الأوسط بين التفاعل والتنافر - وادي, لامية (University of Eloued جامعة الوادي, 2020)
تعد الأسرة في مجتمع المغرب الأوسط العمود الفقري والركيزة الأساسية له،فهي تعتبر أصغر وحدة في التنظيم الاجتماعي، إلا أنها أول بيئة عملية تتولى تنشئة الفرد عبر مراحله المختلفة، فالأسرة هي مؤسسة زوجية حيّة و متفاعلة داخليا وخارجيا، تعتمد على العلاقات التي تربط أفراد الأسرة خاصة الرجل و المرأة، فبقدر ما كانت العلاقة بينهما ودّية و متآلفة ، بقدر ما وجدت حواجز أمامها هزت استقرارها و فرقت الشمل ،و في مقابل ذلك وجدت أطرافا حاولوا احتواء تلك المشاكل و العقبات و إعادة استقرار الأسرة.The small family in the central Maghreb society is considered as the backbone and the main pillar of it, because it is considered as the smallest unit of social organization, it is the first practical environment, which undertakes training of the individual through its different stages, the family is a living conjugal institution, reacts internally and externally. It is based on the relationships that unite the married couple and the elements that constitute the small family. So the more this relationship is friendly and harmonious insofar as there are barriers in front of them which have shaken its stability and dispersed the reunion, on the other hand there are parts, which work and queens on its stability and absorb these problems and litigation, in order to overcome the obstacles and
مقال
Keywords: المغرب الأوسط ; العلاقات الأسرية ; التفاعل ; المشاكل الأسرية